Causas de morte e razões para eutanásia de cães - Fighera, Rafael Almeida (2008)
The ever increasing close contact between dogs and human beings stimulated in last years the production of a great deal of scientific information in canine medicine. However, as the major part of such information stems from work carried on in foreign countries, it is common that Brazilian veterinary clinicians and veterinary pathologists alike have to transpose these data on disease prevalence generated abroad to our situation. Thus, the main objective of this study is to investigate the prevalence of the diseases that culminate with death or motivate the euthanasia of dogs from the midland region of the Midwest of Rio Grande do Sul State, Brazil. In order to achieve this goal the necropsy files of the Laboratório de Patologia Veterinária (LPV) of the Universidade Federal de Santa Maria (UFSM) were accessed and necropsy protocols of dogs necropsied between January 1965 and December 2004 were reviewed in search for information allowing to establish a definitive diagnosis. When circumstances did not allow for a definitive diagnosis the case was considered as inconclusive. During this period 4,844 reports of canine necropsies were filed at the LPVUFSM. The case distribution in relation to the disease categories diagnosed was as follows: infectious and parasitic diseases (1,693 [35.0%]); neoplasms (378 [7.8%]), disorders caused by physical agents (369 [7.6%]), degenerative diseases (342 [7.1%]); poisonings and toxinfections (112 [2.3%]); euthanasia due to convenience (101 [2.1%]), metabolic and endocrinological diseases (97 [2.0%]); iatrogenic disorders (83 [1.7%]); developmental disorders (25 [0.5%]), immune mediate diseases (10 [0.2%]); and nutritional disorders (6 [0.1%]). Other disorders, including multifactorial or idiopathic diseases contributed 80 (1.6%) cases. In 1,548 (32.0%) out of the 4,844 cases it was not possible to establish either cause of death or reason for euthanasia. Infectious and parasitic diseases (mainly canine distemper, parvoviral enteritis and intestinal parasitism), neoplasia (mainly mammary neoplasms and lymphoma), disorders caused by physical agents (mainly accidents caused by automotive vehicles) and degenerative diseases (mainly chronic renal failure, cirrhosis, and congestive heart failure) were the main disease categories that caused death or motivated euthanasia in dogs of this midland region. However when cases were evaluated in relation with the age of the dog, the disease prevalence differs. The main causes of death in puppies were infectious and parasitic disease (mainly parvoviral enteritis, canine distemper, and intestinal parasitism). In adult dogs the most important causes of death were canine distemper, neoplasia and trauma. In age dogs, approximately half of the deaths could be attributed to neoplasia and degenerative disease.